2015
DOI: 10.3390/md13021037
|View full text |Cite
|
Sign up to set email alerts
|

Briarenolides K and L, New Anti-Inflammatory Briarane Diterpenoids from an Octocoral Briareum sp. (Briareidae)

Abstract: Two new briarane-type diterpenoids, briarenolides K (1) and L (2), were isolated from an octocoral identified as Briareum sp. The structures of new briaranes 1 and 2 were elucidated by spectroscopic methods. In the in vitro anti-inflammatory effects test, briaranes 1 and 2 were found to significantly inhibit the accumulation of the pro-inflammatory iNOS protein of the lipopolysaccharide (LPS)-stimulated RAW264.7 macrophage cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 60 publications
0
16
0
Order By: Relevance
“…In the present study, we examined the anti-inflammatory effect of excavatolide B, which is a briarane-type diterpene from soft coral, in in vitro and in vivo models. Recent reports have indicated that some marine briarane-type diterpenes from soft coral also have anti-inflammatory potential in LPS-induced macrophages [ 10 , 11 ] or peptide (FMLP/CB)-induced human neutrophil cell models [ 39 , 40 , 41 ]. Moreover, Wei et al has indicated that excavatolide B can reduce the expression of the pro-inflammatory cytokines IL-6 and TNF-α in an LPS-stimulated mouse bone marrow-derived dendritic cell model [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we examined the anti-inflammatory effect of excavatolide B, which is a briarane-type diterpene from soft coral, in in vitro and in vivo models. Recent reports have indicated that some marine briarane-type diterpenes from soft coral also have anti-inflammatory potential in LPS-induced macrophages [ 10 , 11 ] or peptide (FMLP/CB)-induced human neutrophil cell models [ 39 , 40 , 41 ]. Moreover, Wei et al has indicated that excavatolide B can reduce the expression of the pro-inflammatory cytokines IL-6 and TNF-α in an LPS-stimulated mouse bone marrow-derived dendritic cell model [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Diterpenes from soft coral, such as cembrane and briarane, have been verified to show several bioactivities in previous chemical investigations [ 3 , 6 , 7 ]. Our previous reports also indicate that cembrane- or briarane-type diterpenes from soft coral could have anti-inflammatory potential, significantly inhibiting the expression of proinflammatory proteins, such as inducible nitric oxide synthase (iNOS) and cyclooxygenase (COX-2), in lipopolysaccharide (LPS)-stimulated murine RAW 264.7 macrophages [ 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…843 Eight new briarane-skeletoned diterpenes were reported in 2015 (briarenolides K 1205, L 1206 (ref. 844) and U-Y 1207-1211, 845 Briareum sp. ; dichotellide V 1212, 846 Dichotella gemmacea).…”
Section: Cnidariansmentioning
confidence: 99%
“…ZL0-1b14 [184]; a novel 6,12-dichlorobriarene diterpenoid briarenolide J (165), two briarane diterpenoids briarenolides K and L (166,167), and the briarenolides U-W (168)(169), all compounds isolated from the Taiwanese octocoral Briareum sp. [185][186][187]; two new briarane diterpenoids briaviolides E and I (170,171), isolated from the Taiwanese soft coral Briareum violacea [188]; a new pigmented phenazine compound dermacozine H (172), isolated from the actinomycete Dermacoccus abyssi sp. nov. strain MT1.1, isolated from a Mariana Trench sediment at a depth of 10,898 m [189]; a novel sesquiterpene dysifragilone A (173), isolated from the South China Sea sponge Dysidea fragilis [190]; a new xenicane 4α-hydroxypachylactone (174), isolated from a Chinese brown alga Dictyota plectens [191]; a polyketide comaparvin (175), isolated from the Taiwanese marine crinoid Comanthus bennetti [192]; two novel eunicellin-type diterpenoids hirsutalins N and S (176, 177) and a new tocopherol-derived metabolite hirsutocospiro A (178), isolated from the Taiwanese soft coral Cladiella hirsuta [193][194][195]; a new cembranoid isosinulaflexiolide K (179), isolated from cultured Taiwanese soft corals Sinularia sandensis and Sinularia flexibilis [196]; a novel 9,11-secogorgosteroid klyflaccisteroid F (180), isolated from the Taiwaneses soft coral Klyxum flaccidum [197]; new eunicellin-type diterpenoids krempfielins N (181), Q (182), and R (183), isolated from a Taiwanese soft coral Cladiella krempfi [198,199]; a methylfarnesylquinone (184), isolated from the Taiwanese marine brown alga Homeostrichus formosana [200]; a novel steroid monanchosterol B (185), isolated from the Korean sponge Monanchora sp.…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%
“…nov. strain MT1.1, isolated from a Mariana Trench sediment at a depth of 10,898 m [189]; a novel sesquiterpene dysifragilone A (173), isolated from the South China Sea sponge Dysidea fragilis [190]; a new xenicane 4α-hydroxypachylactone (174), isolated from a Chinese brown alga Dictyota plectens [191]; a polyketide comaparvin (175), isolated from the Taiwanese marine crinoid Comanthus bennetti [192]; two novel eunicellin-type diterpenoids hirsutalins N and S (176, 177) and a new tocopherol-derived metabolite hirsutocospiro A (178), isolated from the Taiwanese soft coral Cladiella hirsuta [193][194][195]; a new cembranoid isosinulaflexiolide K (179), isolated from cultured Taiwanese soft corals Sinularia sandensis and Sinularia flexibilis [196]; a novel 9,11-secogorgosteroid klyflaccisteroid F (180), isolated from the Taiwaneses soft coral Klyxum flaccidum [197]; new eunicellin-type diterpenoids krempfielins N (181), Q (182), and R (183), isolated from a Taiwanese soft coral Cladiella krempfi [198,199]; a methylfarnesylquinone (184), isolated from the Taiwanese marine brown alga Homeostrichus formosana [200]; a novel steroid monanchosterol B (185), isolated from the Korean sponge Monanchora sp. [201]; a oxygenated steroid derivative (186), isolated from the Vietnamese starfish Protoreaster nodosus [202]; a new spirobisnaphthalene rhytidenone C (187), isolated from an extract of a cultured fungal endophyte Rhytidhysteron sp. AS21B isolated from a Thailandese mangrove area [203]; a known terpenoid sarcocrassocolide E (188), isolated from a Taiwanese soft coral Sarcophyton crassocaule [204]; a new cembrane diterpenoid sinulacembranolide A (189), isolated from the Taiwanese soft coral Sinularia gaweli [205]; a new eudesmane-type sesquiterpene thomimarine B (190), isolated from the fungus Penicillium thomii KMM 4667 isolated from the Japanese sea grass Zostera marina [206]; and a novel diterpenoid tortuosene A (191), isolated from the Taiwanese soft coral Sarcophyton tortuosum …”
Section: Anti-inflammatory Activitymentioning
confidence: 99%